Pengaruh Citra Merek Dan Lokasi Outlet Terhadap Minat Beli Konsumen Di Warung Makan Ayam Geprek Preksu Cabang Warungboto Yogyakarta - Sarah Fadillah; Kristiana Sri Utami (Jurnal Bintang Manajemen, 2024)
This research aims to analyze the influence of brand image and outlet location on consumer buying interest at Warung Makan Ayam Geprek Preksu, Warungboto Branch, Yogyakarta. Brand image is an important factor that can influence consumer perceptions of the quality of the products and services offered, while outlet location plays a significant role in determining accessibility and convenience for consumers. The research method used was a survey with a questionnaire distributed to 150 respondents who were customers of the Ayam Geprek Preksu Food Stall. Data analysis was carried out using multiple linear regression to determine the relationship and influence between the variables studied. The research results show that brand image and outlet location significantly influence consumer buying interest, with brand image having a more dominant influence. These findings provide practical implications for the management of Warung Makan Ayam Geprek Preksu to continue to improve its brand image through effective marketing strategies and considering location factors in future business expansion.